DD-024 Development of an objective feedback score for the evaluation of drug and medical device manufacturers/distributors as an additional parameter to be considered in public procurement. (14th February 2016) - Triulzi, I; Trieste, L; Belli, C; Pani, M; Turchetti, G
Abstract : Background: Drugs and medical devices are part of the link between patients and health services. Thus drugs need to be managed properly and should be available and accessible at all times. Indeed, poor management of health resources can contribute, firstly, to a negative impact on health, and secondly, could reduce access and waste money. The current system of public procurement (tendering) does not consider the experiences of public institutions in terms of quality and adherence of manufacturers/distributors in delivering their products according to the undersigned contracts. Penalties paid by manufacturers/distributors for delay and other problems related to the order are not a sufficient stimulus for improving performance. Purpose: The aim was to develop an objective feedback score based on quantitative and qualitative differences between contracts and the characteristics of the delivered orders to evaluate the reputation of the manufacturers/distributors. Material and methods: Based on 14 462 orders of drugs and 19 421 medical devices registered by the drug regional public authority (with a centralised drug and medical device warehouse that supports 18 hospitals and 6 local health units), all of the existing distributors were analysed and a feedback score assigned to them. Results: With a focus on 2014, restricting performance to delivery time (from order to delivery) only, and comparing medians, preliminary results showed that (1) medical device delivery times were higher than those written in the contract; (2) drug suppliers were more reliable than medical device suppliers (ie, median delivery times were lower but still higher than those written in the contract). Conclusion: The score can: (a) better signal the reputation of manufacturers/distributors, giving additional information for commission in public auctions (tendering); (b) give additional information for planning a more efficient system of orders and drug storage; (c) give a simple but powerful instrument to the manufacturers to evaluate their performance, free from the risk of biases of self-evaluation. This tool could be useful in the application of the assessment criteria introduced by EU Directive 24/2014. References and/or Acknowledgements: Area Logistica e Innovazione SIFO. La Farmacologistica. Corso base. Il processo della logistica farmaceutica: prospettive e sfide per il farmacista SSN. IEdizioni Il Campano. ISBN 978–8–86528–247–2. No conflict of interest.